Experimental Study on the Influence of Specimen Shape on Rockburst Proneness of Red Sandstone. (17th August 2020) - Yang, Jiajun; Gong, Fengqiang; Liu, Dongqiao; Liu, Zhixiang
Abstract : To investigate the specimen shape effect on rockburst proneness of rock materials, a string of conventional and single-cycle loading-unloading uniaxial compression tests was performed with cylindrical and cuboid red sandstone specimens. Despite similar development paths on stress-strain curves for the specimens with two shapes, the cuboid specimens generally show a higher uniaxial compressive strength than the cylindrical specimens. The energy evolution laws inside the two shaped specimens were explored. The results show that the input energy density (IED), elastic energy density (EED), and dissipated energy density (DED) of the two shaped specimens increased in a quadratic relationship with the increment of unloading level. Moreover, the linear relationships between the EED, DED, and IED were further confirmed for two shaped specimens, which were defined as the linear energy storage and dissipation laws, respectively. The energy storage coefficients and energy dissipation coefficients (the slopes of the linear relationships between the EED, DED, and IED, respectively) are almost independent of the specimen shape. According to the linear energy storage and dissipation laws, the peak EED and peak DED of every specimen can be calculated accurately. Finally, combining the failure process of rock specimens recorded by a high-speed camera, the elastic energy index (W ET ), the residual elastic energy index ( A EF ), and the far-field ejection mass ratio ( M F ) of each specimen were adopted to assess the rockburst proneness of the red sandstone sampled in cylindrical and cuboid. The results show that cuboid specimens exhibited stronger rockburst proneness than cylindrical ones, which favorably agreed with the actual failure phenomena.